ZF protein C2H2-71 regulates the soluble solids content in tomato by inhibiting LIN5 - Fangman Li; Junshen Lin; John Kojo Ahiakpa; Wenxian Gai; Jinbao Tao; Pingfei Ge; Xingyu Zhang; Yizhuo Mu; Jie Ye; Yuyang Zhang (Journal of Integrative Agriculture, 2025)
Soluble solids content (SSC) plays an important role in determining the flavor of tomato fruits. Tomato fruit SSC is transcriptionally regulated via sugar metabolism. Previous studies have predominantly focused on the role of C2H2-type zinc finger proteins in tomato growth and development. However, the specific regulatory mechanisms of C2H2 in the accumulation of soluble solids in tomato fruits are not fully understood. This study used eight tomato accessions with varying levels of SSC to study the expression of SlC2H2 family genes in red ripe fruits. The levels of SlC2H2-71 expression were found to be significantly reduced in high-SSC accessions compared to low-SSC accessions. Several Slc2h2-71 mutant lines were developed using the CRISPR-Cas9 system, which led to elevated levels of soluble solids, fructose, glucose, malic acid, and citric acid in mature red ripe fruits. However, the sucrose content in the edited Slc2h2-71 mutant lines was generally lower. RNA-seq analysis revealed that fruits from the mutant lines had altered expression of genes related to the sugar and acid metabolic pathways, which was further confirmed by quantitative real-time PCR. Specifically, the expression of SlLIN5 encoding the cell wall invertase (CWIN) was elevated. The yeast one-hybrid (Y1H) assay, 35S::UAS-GUS, dual-luciferase reporter systems and electrophoretic mobility shift assay (EMSA) demonstrated that C2H2-71 regulates tomato sugar metabolism by directly binding to the promoter region of SlLIN5, culminating in the repression of its transcriptional activity. The activity of acid invertase exhibited a significantly higher level in the SlC2H2-71 knock-out lines compared to the control lines. In summary, the regulation of tomato fruit SSC by C2H2-71 involves the inhibition of SlLIN5 expression.